2020
DOI: 10.1155/2020/8436951
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Norovirus Strains Isolated from Older Children and Adults in Impoverished Communities of Vhembe District, South Africa

Abstract: Background. Human norovirus (NoV) is an etiological agent associated with acute gastroenteritis (AGE) in both children and adults worldwide. However, very few studies have been reported on the prevalence and genetic diversity of NoV strains in children older than 5 years of age and adults with little or inadequate water and sanitation conditions. Objectives. The aim of this study was assessing the prevalence of the human norovirus in older children and adults suffering with diarrhoea from rural communities in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Though previous studies have reported NoV causing acute gastroenteritis associated with moderate to severe diarrhea disease [55,56], the current study, compared to other recent AGE etiology investigations, found NoV infections to be associated with severe AGE [57][58][59]. Of note, previous NoV surveys in the study area did not report a high presence of dehydrating diarrhea as revealed in the current study [25,60]. There was a rise in dehydration cases associated with an enhanced NoV activity over years in the study area (Figure 1).…”
Section: Discussioncontrasting
confidence: 61%
“…Though previous studies have reported NoV causing acute gastroenteritis associated with moderate to severe diarrhea disease [55,56], the current study, compared to other recent AGE etiology investigations, found NoV infections to be associated with severe AGE [57][58][59]. Of note, previous NoV surveys in the study area did not report a high presence of dehydrating diarrhea as revealed in the current study [25,60]. There was a rise in dehydration cases associated with an enhanced NoV activity over years in the study area (Figure 1).…”
Section: Discussioncontrasting
confidence: 61%
“…2017 South Africa South Africa Cohort < 5 Multiplex PCR 205 32 28 [ 26 ] Nxele et al (2017) June–August 2014 South Africa South Africa Cross-sectional < 5 Rt-qPCR 182 41 None [ 62 ] Molondo et al (2020) August 2017–Oct. 2018 South Africa South Africa Cross-sectional < 5 Rt-qPCR 80 13 4 [ 27 ] Tatay et al (2018) June–May 2017 Sudan North Africa Cross-sectional < 5 Rt-qPCR 66 19 None [ 63 ] Elsayed et al (2019) Jan. 2018–May 2019 Egypt North Africa Cross-sectional < 18 Rt-qPCR 200 61 None [ 64 ] Lartey et al (2020) Jan. 2008–Dec. 2017 Ghana West Africa Surveillance ...…”
Section: Resultsmentioning
confidence: 99%
“…The highest prevalence of GI NoVs was reported in a study conducted in Angola. Most the included articles used open reading frame-2 (ORF-2) for genotyping and or sequencing, but some studies [ 12 , 19 , 20 , 26 , 27 ] used dual systems of genotyping using both ORF-1 and ORF-2.…”
Section: Resultsmentioning
confidence: 99%
“…Recent epidemiological studies in South Africa showed substantial prevalence in urban hospitalized settings [10][11][12]; however, more data which includes both symptomatic and asymptomatic carriers in hospitalized and outpatients from rural community settings are needed to estimate the total prevalence of astrovirus circulating in the country. Previous studies showed high prevalence of enteric viruses in the Vhembe District suggesting frequent exposure of children to enteric pathogens [13,14]. Therefore, this study aimed to investigate the symptomatic and asymptomatic prevalence of classic human astrovirus strains circulating in the Vhembe District among hospitalized and outpatient children.…”
Section: Introductionmentioning
confidence: 98%